Pancasila Sebagai Entitas Dan Identitas Bangsa Indonesia Dan Perwujudannya Di SMAN 5 Palangka Raya - Safitri Anggita Tunjung Sari; Misnawati Misnawati; Rusdiansyah Rusdiansyah; Lutfi Aji Taufandy; Sri Maya; Riwi Nitiya (Cakrawala: Jurnal Pengabdian Masyarakat Global, 2023)
Pancasila has an important role as the entity and identity of the Indonesian nation. Without an entity and identity, the Indonesian nation does not have an identity and characteristics as a society with a state. Especially with the increasingly rapid flow of globalization, it is feared that the ideology of Pancasila is increasingly being eroded within Indonesian society. There is the concern, so that has become a shared duty and responsibility in preserving and passing on Pancasila to the next generation so that the ideology of Pancasila as the basis of this country remains firmly attached to each individual. One form of effort to preserve and pass on Pancasila to the next generation is the application of Pancasila Student Profiles to learning materials in schools. There are six dimensions in the Pancasila Student Profile, including: 1) Faithful, devoted to God Almighty, and noble, 2) Global diversity, 3) Mutual cooperation, 4) Independent, 5) Critical thinking, and 6) Creative. The existence of the Pancasila Student Profile is expected to liberate and develop the competencies or abilities of students according to their characteristics and become democratic citizens as well as become superior and productive human beings in the 21st Century. Therefore, it is hoped that Indonesian students will be able to participate in global development that is sustainable and resilient in facing various challenges. These problems were researched and studied using literature and also combining the results of PPL observations conducted at SMAN 5 Palangka Raya.